Catalyst to Connection: When Technical Difficulties Lead to Social Support for Older Adults. (August 2018) - Francis, Jessica; Kadylak, Travis; Makki, Taj. W.; Rikard, R. V.; Cotten, Shelia R.
Information and communication technology (ICT) use can mitigate the negative impact of various age-related threats, such as isolation and loneliness, by facilitating connection with social ties and access to social support. Although research regarding various uses and benefits of ICTs among older adults has increased, there is limited research regarding the impact of technical difficulties on older adults' well-being. Our study explores technical difficulties encountered, how older adults cope with ICT failure, and the various forms of social support that may result as a consequence of accessing technical support. We use data from nine semistructured focus groups conducted with older adults in the Midwest region of the United States. Results show that older adults may adapt new strategies for coping with the technical difficulties that arise from regular ICT use. Furthermore, as older adults incorporate ICTs into their daily lives and seek assistance from social ties and experts, they may also be indirectly combating the threat of isolation and loneliness.